Mathematical Problem Solving for Students in the Superior Intelligence Quotient (IQ) Category - Suci Wulandari; Elly Susanti; Sri Harini (MEJ (Mathematics Education Journal), 2021)
The purpose of this study is to describe the mathematical problem solving of students in the superior intelligence quotient (IQ) category. This research was conducted at MAN 1 Trenggalek because the school had already conducted an IQ test. This study uses a qualitative approach with an exploratory descriptive type. The subjects in this study were students who had done an IQ test with a superior IQ. This study will describe 2 subjects based on relatively similar tendencies. Data collection techniques used documentation studies on IQ, math problem solving, think aloud, and semi-structured interviews. Data analysis in this study refers to Polya's research on mathematical problem solving. The validity of the data in this study used triangulation techniques. The results of this study indicate that students with superior IQ are able to fulfill the stages of solving mathematical problems, namely understanding the problem, planning strategies, implementing plans, and evaluating. It is shown that superior IQ students are able to solve problems according to problem solving procedures with the abilities possessed by superior IQ category students.